2012
DOI: 10.1007/s11207-012-0150-2
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Oscillations in a Global Solar Dynamo

Abstract: We characterize and analyze rotational torsional oscillations developing in a large-eddy magnetohydrodynamical simulation of solar convection (Ghizaru, Charbonneau, and Smolarkiewicz, Astrophys. J. Lett. 715, L133 (2010); Racine et al., Astrophys. J. 735, 46 (2011)) producing an axisymmetric largescale magnetic field undergoing periodic polarity reversals. Motivated by the many solar-like features exhibited by these oscillations, we carry out an analysis of the large-scale zonal dynamics. We demonstrate that s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 31 publications
3
56
2
Order By: Relevance
“…Indeed, Spruit (2003) considered the proposition that oscillations are driven by temperature variations at the surface, which are due to the enhanced emission of small magnetic structures. In contrast, recent numerical simulations by Beaudoin et al (2013) showed that the TO can be driven via the magnetic modulation of the angular momentum transport by the large-scale meridional flow.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Indeed, Spruit (2003) considered the proposition that oscillations are driven by temperature variations at the surface, which are due to the enhanced emission of small magnetic structures. In contrast, recent numerical simulations by Beaudoin et al (2013) showed that the TO can be driven via the magnetic modulation of the angular momentum transport by the large-scale meridional flow.…”
Section: Introductionmentioning
confidence: 81%
“…This suggests that the TO are of magnetic origin. For instance, they may be driven directly through the large-scale magnetic torque, but also indirectly via the transport of angular momentum by meridional flow modulated by the magnetic cycle, as suggested by Beaudoin et al (2013).…”
Section: Understanding Torsional Oscillationsmentioning
confidence: 99%
“…Being intermittent and adaptive, the residual dissipation facilitate the model to perform ILESs that mimics the action of explicit subgrid-scale turbulence models, whenever the concerned advective field is under-resolved (Margolin et al 2006). Such ILESs performed with the model have already been successfully utilized to simulate regular solar cycles (Ghizaru et al 2010), with the rotational torsional oscillations subsequently characterized and analyzed in (Beaudoin et al 2013). The simulations reported continue relying on the effectiveness of ILES in regularizing the onset of MRs, concurrent and collocated with developing CSs (Kumar et al 2013).…”
Section: Numerical Modelmentioning
confidence: 99%
“…Due to computing limitations all these simulations run in parameter regimes still far removed from solar interior conditions. Nonetheless, many are producing tantalizingly solar-like features, including rotational torsional oscillations (Beaudoin et al 2013) equatorward propagation of activity "belts" (Käpylä et al 2012;Warnecke et al 2014;Augustson et al 2015) cyclic in-phase magnetic modulation of convective energy transport (Cossette et al 2013) and Grand Minima-like interruptions of cyclic behavior (Augustson et al 2015). One particularly interesting feature is the spontaneous production of magnetic flux tube-like structures within the convection zone, as reported in Nelson et al (2013).…”
Section: Sun-in-timementioning
confidence: 99%